2023
DOI: 10.1039/d3cy00026e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating metal oxide support effects on the RWGS activity of Mo2C catalysts

Abstract: Mo2C supported on nonreducible metal oxides shows increased activity for the reverse water gas shift reaction compared to reducible oxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…The effect of the oxide support's (γ-Al 2 O 3 , SiO 2 , ZrO 2 , CeO 2 , and MgO) reducibility and acidity on Mo 2 C which promoted by K were investigate by same team. [89] The K-promoted Mo 2 C/ Al 2 O 3 catalyst demonstrated the highest CO 2 conversion at 18.2 % with a selectivity towards CO of 95.2 % at 300 °C and 19.3 bar with a mixture of N 2 , H 2 and CO 2 where the ratio of H 2 : CO 2 was 3 : 1 and N 2 , used as an internal standard, comprised 16.5 % of the gaseous mixture. The results showed that nonreducible and acidic supports, KÀ Mo 2 C/Al 2 O 3 , were the most active for the production of CO. An efficient non-noble metal catalyst, single Mo atoms anchored on N-doped porous carbon, was designed for RWGS reaction.…”
Section: Other-based Catalystmentioning
confidence: 94%
“…The effect of the oxide support's (γ-Al 2 O 3 , SiO 2 , ZrO 2 , CeO 2 , and MgO) reducibility and acidity on Mo 2 C which promoted by K were investigate by same team. [89] The K-promoted Mo 2 C/ Al 2 O 3 catalyst demonstrated the highest CO 2 conversion at 18.2 % with a selectivity towards CO of 95.2 % at 300 °C and 19.3 bar with a mixture of N 2 , H 2 and CO 2 where the ratio of H 2 : CO 2 was 3 : 1 and N 2 , used as an internal standard, comprised 16.5 % of the gaseous mixture. The results showed that nonreducible and acidic supports, KÀ Mo 2 C/Al 2 O 3 , were the most active for the production of CO. An efficient non-noble metal catalyst, single Mo atoms anchored on N-doped porous carbon, was designed for RWGS reaction.…”
Section: Other-based Catalystmentioning
confidence: 94%
“…Transition metal carbide catalysts (TMCs) are also promising and attractive catalysts; after the introduction of carbon, the electronic properties of these catalysts change, meaning that their activity becomes similar to that of precious metal catalysts, with a strong H 2 dissociation and CO bond-breaking ability, and showing high activity in the CO 2 hydrogenation to CO reaction. Therefore, it has been reported that catalysts such as vanadium carbide [140], tungsten carbide [141,142], cobalt carbide [143], and molybdenum carbide [126,[144][145][146][147][148][149] have superior catalytic activity and CO selectivity when applied to RWGS reactions.…”
Section: Transition Metal Carbide Catalystsmentioning
confidence: 99%
“…In this context, transition metal carbides, particularly molybdenum carbides, show promise because their components are earth-abundant and because these materials can catalyze some chemical transformations with noble metal–like behavior ( 16 ). However, the synthesis of molybdenum carbide materials is either complex ( 17 , 18 ) or requires noble metals to achieve certain active phases ( 19 , 20 ).…”
mentioning
confidence: 99%